2021
DOI: 10.1017/aog.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of hot-point drilling in ice

Abstract: Hot-point drills have been widely used for drilling boreholes in glaciers, ice caps and ice sheets. A hot-point drill melts ice through the thermal head at its bottom end. Penetration occurs through a close-contact melting (CCM) process, in which the ice is melted, and the meltwater is squeezed out by the exerted force applied on the thermal head. During the drilling, a thin water film is formed to separate the thermal head from the surrounding ice. For the hot-point drill, the rate of penetration (ROP) is inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We originally chose a parabolic nose shape based on Shreve (1962), who proposed that nose shape has a significant impact on the efficiency of a thermal probe. However, a recent numerical study (Li et al 2021) subsequently suggested that the shape of the nose might not be as influential on the descent speed as previously hypothesized. In addition, system-level metrics that enable likefor-like comparisons between nose geometries have not yet been developed (e.g., ensuring that different geometries have the same carrying capacity), and the confounding variable of operational efficiency ò has not been sufficiently accounted for in any comparisons.…”
Section: Cryogenic Probe Designsmentioning
confidence: 89%
See 1 more Smart Citation
“…We originally chose a parabolic nose shape based on Shreve (1962), who proposed that nose shape has a significant impact on the efficiency of a thermal probe. However, a recent numerical study (Li et al 2021) subsequently suggested that the shape of the nose might not be as influential on the descent speed as previously hypothesized. In addition, system-level metrics that enable likefor-like comparisons between nose geometries have not yet been developed (e.g., ensuring that different geometries have the same carrying capacity), and the confounding variable of operational efficiency ò has not been sufficiently accounted for in any comparisons.…”
Section: Cryogenic Probe Designsmentioning
confidence: 89%
“…Brandt et al (2019) provide two models: the first is a precursor to the numerical model in Durka et al (2022) below, but using a heuristic approach to estimate v; the second is a semianalytical extension of the Aamot model addressing assumption (a) via finite element modeling and includes ò as a model input parameter. Li et al (2021) focus purely on the Startup Phase in warm ice using detailed numerical simulations. Durka et al (2022) introduce two models: the analytical Aamot+ model, which relaxes assumption (a) via an experimental fit to the temperature dependence of the thermophysical properties of pure water ice, and the Aamot++ model, which extends this to address assumption (c) by explicitly positing an (unknown) water jacket thickness to estimate ò.…”
Section: Modeling Backgroundmentioning
confidence: 99%
“…We simulate borehole refreezing using a 1-D radial heat transfer model. This model is relatively simple in comparison to other models describing processes at the interface between the melt tip and surrounding ice (Li et al, 2021b). Our model consists of an enthalpy-based formulation of heat diffusion and latent energy exchange across a moving waterice phase boundary (Greenler et al, 2014).…”
Section: Discussion: Borehole Refreezingmentioning
confidence: 99%
“…We simulate borehole refreezing using a 1-D radial heat transfer model. This model is relatively simple in comparison to other models describing processes at the interface between the melt tip and surrounding ice [Li et al, 2021b]. Our model consists of an enthalpy-based formulation of heat diffusion and latent energy exchange across a moving water-ice phase boundary [Greenler et al, 2014].…”
Section: Discussion: Borehole Refreezingmentioning
confidence: 99%